2022
DOI: 10.1007/s10901-022-09984-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of jobs, amenities, and locations on housing submarkets in Xiamen City, China

Abstract: Numerous studies have found that jobs, amenities, and location influence housing prices in urban areas. However, there is still a lack of in-depth understanding of the impacts of these factors on various housing submarkets within a city. With the case study of Xiamen, this paper investigates the impacts of jobs, amenities, and location on four housing submarkets, classified by owner-occupied and rental housing, in inner and outer districts. The hedonic model, Chow test, and Tiao-Goldberger test are applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Shin et al (2024) found that accessibility to various urban amenities significantly influences housing prices, for instance access to learning, care, education and leisure facilities. The impact of public transport infrastructure on housing prices has been confirmed in a number of recent studies (Efthymiou & Antoniou, 2013;Song et al, 2019;Li et al, 2023). Using proximity-and accessibility-based measures for estimating the impact of transport infrastructure on housing prices, the research indicates that proximity to the big transportation hubs, such as airports, bus terminals, and road intersections adversely impacts individual housing price, opposite to transportation accessibility measured by proximity to rapid transit or public bike stations (Soltani et al, 2024) The impact of tourism expansion on housing prices at municipal levels has been extensively researched and confirmed (Biagi et al, 2015;Paramati & Roca, 2019;Alola et al, 2020).…”
Section: Selective Review Of Empirical Literaturementioning
confidence: 84%
“…Shin et al (2024) found that accessibility to various urban amenities significantly influences housing prices, for instance access to learning, care, education and leisure facilities. The impact of public transport infrastructure on housing prices has been confirmed in a number of recent studies (Efthymiou & Antoniou, 2013;Song et al, 2019;Li et al, 2023). Using proximity-and accessibility-based measures for estimating the impact of transport infrastructure on housing prices, the research indicates that proximity to the big transportation hubs, such as airports, bus terminals, and road intersections adversely impacts individual housing price, opposite to transportation accessibility measured by proximity to rapid transit or public bike stations (Soltani et al, 2024) The impact of tourism expansion on housing prices at municipal levels has been extensively researched and confirmed (Biagi et al, 2015;Paramati & Roca, 2019;Alola et al, 2020).…”
Section: Selective Review Of Empirical Literaturementioning
confidence: 84%
“…Micro determinants are those related to the specific characteristics of real estate. According to the literature, these determinants are classified into three categories, namely structural attributes, locational attributes, and neighborhood qualities [5,7,8,11,17,32,33].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…They concluded that the customer's willingness to pay for a built square meter is greater than an extra square meter on the home's lot. In the approach presented by Li et al [32], which used real estate sales and rental prices for both internal and external districts, the area of the property had a positive influence.…”
Section: Structural Attributesmentioning
confidence: 99%
See 1 more Smart Citation